Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/bit.10514
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of reactive and stable glucose oxidase‐containing liposomes modulated with detergent

Abstract: Glucose oxidase-containing liposomes (GOL) as well as detergent-modulated glucose oxidase-containing liposomes were prepared and characterized, focusing not only on the reactivity of the liposomes upon external addition of glucose but also on the leakage of the entrapped glucose oxidase (GO) from the liposomes with the aim of developing a reactive and stable liposomal GO system. The membranes of the GOL prepared were composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and modulated with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…The time course of hydrogen peroxide produced by the GO-catalyzed oxidation of glucose was measured by the horseradish peroxidase-catalyzed formation of oxidized o-dianisidine, as a measure of GO activity. The detailed procedure for the assay is described in our previous works Yoshimoto et al, 2003).…”
Section: Measurements Of Glucose Oxidase (Go) Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The time course of hydrogen peroxide produced by the GO-catalyzed oxidation of glucose was measured by the horseradish peroxidase-catalyzed formation of oxidized o-dianisidine, as a measure of GO activity. The detailed procedure for the assay is described in our previous works Yoshimoto et al, 2003).…”
Section: Measurements Of Glucose Oxidase (Go) Activitymentioning
confidence: 99%
“…There are at least two methods to increase the permeability of the liposome membrane towards substrates. One is to modify the membrane with low concentrations of a micelleforming detergent (Treyer et al, 2002;Yoshimoto et al, 2003). But this method is not applicable to the above bioreactor because of foam formation induced by the free (not membrane-bound) detergent present in the bulk solution.…”
Section: Introductionmentioning
confidence: 98%
“…To verify and quantify the formation of mixed POPC/cholate liposomes, R e sat and K (described below) were determined by turbidity measurements as described before (Paternostre et al, 1988;Lichtenberg, 1996;Treyer et al, 2002;Yoshimoto et al, 2003) The enzymatic activity of proteinase K was measured immediately after mixing a proteinase K solution with a cholate or POPC/cholate mixed micelle solution, or with a POPC suspension. The POPC/cholate mixed liposomes were first equilibrated for 15 -17 h at room temperature before mixing the proteinase K solution.…”
Section: Characterization Of Proteinase K-containing Liposomes Modulamentioning
confidence: 99%
“…It has, however, recently been reported that the reactivity of an enzyme inside liposomes can be controlled by modulating the lipid membranes with detergents such as sodium cholate and Triton X-100 to form lipid/detergent mixed liposomes with minimal enzyme leakage (Annesini et al, 1997;Treyer et al, 2002;Yoshimoto et al, 2003). In this way, the apparent substrate selectivity of an enzyme inside liposomes could be controlled through an alteration of the membrane permeability caused by the detergent molecules.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation